"Here comes Bio-me": An analysis of a biobank campaign targeted at children. (October 2021) - Snell, Karoliina; Tarkkala, Heta
Finnish biobanks have started to recruit children. The national supervising authority has emphasized the centrality of providing children with age-appropriate information. We analyzed one such campaign. We argue that by simplifying the complex socio-technical arrangements of biobanking with the introduction of a new metaphor-like concept, "Bio-me, " the campaign presents a misleading and reductionist picture of data-driven biomedicine and biobank participation. First, the Bio-me character seems to bear similarities to the seventeenth-century explanations of embryological development. Second, the focus in the campaign is on biological material while crucial connections to different sorts of data are ignored. Third, we point to the absence of verbal references to genes and DNA, although the prevailing visualization comprises the double helix. We argue that the campaign has potential to contribute to public misunderstanding of science by introducing a new term that has little connection to actual biology or scientific practices it tries to promote.